Instructional Design of Problem-Based Learning Models: A Strategy for Improving Students' Critical Thinking Abilities in Learning News Texts - Fitriyah, Ayu; Ayatin, Rika; Sugiarti, Rya; Rozak, Abdul; Pujiatna, Tri (Journal of Languages and Language Teaching, 2024)
This research addresses the need to enhance critical thinking skills in junior high school students through effective instructional design, particularly in the context of learning news texts. The study is based on the premise that problem-based learning (PBL) can significantly improve students' critical thinking by engaging them in real-world problem-solving scenarios. Given the growing emphasis on critical thinking as a core educational objective, it is essential to develop instructional models that not only teach content but also foster higher-order thinking skills. The primary aim of this research is to design an instructional model for teaching news texts in junior high school and to assess its validity and effectiveness. The study employed a Research and Development (R&D) approach, utilizing the ADDIE model, which involves five stages: Analysis, Design, Development, Implementation, and Evaluation. Following the development of the instructional design, it underwent validation by both learning experts and practitioners. The validation process yielded high scores, with learning experts rating it at 95.83% and practitioners at 88.89%, resulting in an overall average validity score of 92.36%, categorizing the design as highly valid. In practice, the problem-based learning model was implemented in classrooms, and its impact on students' learning outcomes was evaluated. The students achieved an average learning score of 86%, indicating the instructional design's effectiveness in delivering content. Furthermore, the assessment of students' critical thinking skills showed an average score of 79%, placing it in the "good" category. These findings suggest that the PBL-based instructional design is effective in not only teaching news texts but also in enhancing students' critical thinking skills, making it a valuable approach for junior high school education.